Remodeling of Membrane Properties and Dendritic Architecture Accompanies the Postembryonic Conversion of a Slow into a Fast Motoneuron - Duch, Carsten (J Neurosci, 2000)
The postembryonic acquisition of behavior requires alterations in neuronal circuitry, which ultimately must be understood as specific changes in neuronal structure, membrane properties, and synaptic connectivity. This study addresses this goal by describing the postembryonic remodeling of the excitability and dendritic morphology of an identified motoneuron, MN5, which during the metamorphosis ofManduca sexta (L.) changes from a slow motoneuron that is involved in larval-crawling behavior into a fast adult flight motoneuron. A fivefold lower input resistance, a higher firing threshold, and an increase in voltage-activated K(+)current contribute to a lower excitability of the adult MN5, which is a prerequisite for its newly acquired behavioral role. In addition, the adult MN5 displays larger Ca(2+) currents. The dendrites of MN5 undergo extensive remodeling. Drastic regression of larval dendrites during early pupal stages is followed by rapid growth of new dendrites. Critical changes in excitability take place during the onset of adult dendrite formation. Larval Ca(2+)currents are absent when dendritic remodeling is most dramatic but increase markedly during later development. Changes in Ca(2+) and K(+) currents follow different time courses, allowing the transient occurrence of Ca(2+) spikes during pupal stages when new dendritic branching ceases. The adult MN5 can produce prolonged Ca(2+) spikes after K(+) currents are reduced. We suggest that alterations in Ca(2+) and K(+) currents are necessary for the participation of MN5 in flight behavior and that the transient production of Ca(2+) spikes may influence postembryonic dendritic remodeling.